PENERAPAN STRATEGI THINK-TALK-WRITE (TTW) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA DI SMP NEGERI 1 BANGKO - Antonius Nainggolan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
During the COVID-19 pandemic, the learning process, which is usually carried out face-to-face in front of the class, can no longer be carried out, resulting in the change of the learning system to online. This study aims to improve students' understanding of mathematical concepts at SMP Negeri 1 Bangko with the research method used is Classroom Action Research (CAR). CAR comes from the west known as Classroom Action Research (CAR). As stated by Arikunto, CAR is research conducted in the classroom with the aim of improving or improving the quality of learning practices. The results obtained about the understanding of students' concepts before conducting the class action research showed an average class of 63.50 with the number of students who completed 13 people with a classical percentage of 42%. In the first cycle, the average class obtained was 69.83 with a total of 20 people who completed with a percentage of the classical number of 65%. The increase occurred in the second cycle with an average class of 81 with the number of students who completed 31 people with a percentage of the classical number of 100% so that it can be concluded that using the Think Talk Write (TTW) strategy can improve understanding of mathematical concepts.